On the Use of Concept Maps as an Assessment Tool in Science: What we have Learned so Far - María Araceli Ruiz Primo (Universidad Autónoma de Baja California, 2000)
In this paper I describe concept maps as an assessment tool to measure one aspect of achievement, the organization of propositional (declarative) knowledge in a domain. A concept map-based assessment consists of a task that elicits structured knowledge, a response format, and a scoring system. Variation in tasks, response formats, and scoring systems produce different mapping techniques that may elicit different knowledge representations, posing construct-interpretation challenges. This paper provides an overview of the research on the technical characteristics of concept maps. It briefly describes some of the studies that have been conducted to this end, and what we have learned so far about this form of assessment.